Midwife's Knowledge Of Neuromusculoskeletal Disorders in Pregnant Women - Lia Dwi Prafitri; Wahyu Ersila (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Neuromusculoskeletal changes in pregnancy often cause discomfort problems as the pregnancy ages. The increased prevalence of the incidence of neuromusculoskeletal disorders during the third trimester of pregnancy, namely low back pain 63%, muscle cramps 60.2% and carpal tunnel syndrome 6.8% needs special attention by midwives. Efforts to increase knowledge and motivation in carrying out pregnancy examination services play an important role in reducing maternal mortality. The purpose of this study is to find out the relationship of midwives' knowledge about neuromusculoskeletal disorders in pregnant women with the motivation of midwives in overcoming neuromusculoskeletal disorders in pregnant women. This research is correlative descriptive with a cross sectional approach. Sampling techniques using cluster sampling and obtained a number of 100 midwives. The chi square test result obtained the value p value = 0.022 and the value OR = 10.213. There is a significant relationship between the midwife's knowledge of neuromusculoskeletal disorders of pregnant women and the motivation of midwives in overcoming neuromusculoskeletal disorders in pregnant women. Well-informed midwives had a high chance of overcoming neuromusculoskeletal disorders in pregnant women by 10,213 times compared to reasonably knowledgeable midwives. Midwives are expected to always increase the latest knowledge by participating in training activities or further studies and the Health Service is expected to provide support to midwives by providing facilities and infrastructure to increase the knowledge and motivation of midwives.